Clinical and virological outcomes of TB/HIV co-infected patients treated with dolutegravir-based HIV antiretroviral regimens: Programmatic experience from Botswana - Modongo, Chawangwa (J Acquir Immune Defic Syndr, 2019)
BACKGROUND: Dolutegravir (DTG) has recently been recommended as a preferred first-line regimen for the treatment of new and treatment experienced HIV infected patients. However, potential drug interactions between DTG and rifampicin remain a clinical and public health concern. METHODS: We analyzed HIV and TB treatment outcomes of HIV-infected patients concomitantly receiving rifampicin- and DTG-based regimens under programmatic conditions in Botswana. The outcomes of interest were successful TB treatment and viral load suppression. We used multivariable logistic models to determine predictors for each outcome of interest. RESULTS: A total of 1,225 patients were included in the analysis to evaluate predictors of successful TB outcome. Among patients on DTG and non-DTG regimens, 90.9% and 88.3% achieved favorable TB treatment outcomes, respectively. Of those who received DTG-based regimen; 44% received once-daily dosing and 53% twice-daily dosing. We found that DTG was associated with favorable TB treatment outcome (adjusted odds ratio [aOR] = 1.56; 95% confidence interval [CI] = 1.06, 2.31), after adjusting for age, gender, and CD4 cell counts. High rates of viral load suppression were found across all ART regimen categories (>92% for all). We did not find an independent association between DTG and viral suppression after adjustment of other covariates CONCLUSIONS: The use of DTG-based ART regimens in patients coinfected with TB and HIV lead to favorable TB and HIV treatment outcomes, comparable to those achieved with alternative ART regimens. Our results provide reassurance to TB and HIV programs about the overall programmatic concomitant use of these first-line treatment regimens for the management of HIV and TB coinfected patients.